Body Fat Distribution and Systolic Blood Pressure in 10, 000 Adults with Whole‐Body Imaging: UK Biobank and Oxford BioBank. Issue 7 (13th May 2019) - Malden, Deborah; Lacey, Ben; Emberson, Jonathan; Karpe, Fredrik; Allen, Naomi; Bennett, Derrick; Lewington, Sarah
Abstract : Objective: This study aimed to quantify the associations of regional fat mass and fat‐free mass with systolic blood pressure. Methods: This analysis combined individual participant data from two large‐scale imaging studies: UK Biobank and Oxford BioBank. In both studies, participants were interviewed and measured, and they underwent dual‐energy x‐ray absorptiometry imaging. Linear regression was used to relate systolic blood pressure to anthropometric measures of adiposity (BMI, waist circumference, and waist to hip ratio) and dual‐energy x‐ray absorptiometry–derived measures of body composition (visceral android fat, subcutaneous android fat, subcutaneous gynoid fat, and fat‐free mass). Results: Among 10, 260 participants (mean age 49; 96% white), systolic blood pressure was positively associated with visceral android fat (3.2 mmHg/SD in men; 2.8 mmHg/SD in women) and fat‐free mass (1.92 mmHg/SD in men; 1.64 mmHg/SD in women), but there was no evidence of an association with subcutaneous android or gynoid fat. Associations of systolic blood pressure with BMI were slightly steeper than those with waist circumference or waist to hip ratio; these associations remained unchanged following adjustment for fat‐free mass, but adjustment for visceral android fat eliminated associations with waist circumference and waist to hip ratio and more than halved associations with BMI. Conclusions: This analysis indicates that visceral fat is the primary etiological component of excess adiposity underlying the development of adiposity‐related hypertension.